Electron Bulk Heating at Saturn's Magnetopause. Issue 5 (2nd May 2021) - Cheng, I.; Achilleos, N.; Masters, A.; Lewis, G.; Kane, M.; Guio, P.
Abstract: Magnetic reconnection at the magnetopause (MP) energizes ambient plasma via the release of magnetic energy and produces an "open" magnetosphere allowing solar wind particles to directly enter the system. At Saturn, the nature of MP reconnection remains unclear. The current study examines electron bulk heating at MP crossings, in order to probe the relationship between observed and predicted reconnection heating proposed by Phan et al. (2013, https://doi.org/10.1002/grl.50917 ) under open and closed MP, and how this may pertain to the position of the crossings in the Δ β ‐magnetic shear parameter space. The electron heating for 70 MP crossings made by the Cassini spacecraft from April 2005 to July 2007 was found using 1d and 3d moment methods. Minimum variance analysis was used on the magnetic field data to help indicate whether the MP is open or closed. We found better agreement between observed and predicted heating for events suggestive of locally "open" MP. For events suggestive of locally "closed" MP, we observed a cluster of points consistent with no electron heating, but also numerous cases with significant heating. Examining the events in the Δ β ‐magnetic shear parameter space, we find 83% of events without evidence of energization were situated in the "reconnection suppressed" regime, whilst between 43% to 68% of events with energization lie in the "reconnection possible" regime depending on the threshold used. The discrepancies could be explained by a combination of spatial and temporal variability which makes it possible to observe heated electrons with different conditions from the putative reconnection site. Plain Language Summary: Saturn's magnetic cavity in space is marked by a boundary called the magnetopause. Particles from the Sun can enter this region via a process called magnetic reconnection. However, the conditions under which this process can occur on the boundary remains unclear. We used the heating of electrons detected by the Cassini spacecraft during crossings of this boundary to study the effects of different conditions on the viability of reconnection at Saturn's magnetopause. We found that most of the crossings which showed evidence of significant electron heating close to theoretical predictions were also at locations where the magnetopause was open (i.e., locations where solar particles can enter Saturn's territory) and/or where the local conditions were suitable for reconnection to take place. Key Points: Electron bulk heating at Saturn's magnetopause is used to test hypotheses about magnetic reconnection Observations suggestive of locally open magnetopause tend to exhibit electron heating closer to the theoretical prediction for reconnection ΔBeta magnetic shear parameter space discriminates well between events with evidence of energization and those without